MACC1 Is Associated With Epithelial–Mesenchymal Transition and Can Predict Poor Prognosis in Nasopharyngeal Carcinoma - Cheng, Hao; Zhou, Linxiang; Long, Yalan; Xiang, Juanjuan; Chen, Longhua (Frontiers in Oncology, 2021)
Background: Given the reported correlation between the oncogene metastasis-associated in colon cancer 1 (MACC1) and nasopharyngeal carcinoma (NPC), as well as between MACC1 and epithelial–mesenchymal transition (EMT), we speculated that EMT is a likely causative link between MACC1 expression and poor NPC prognosis. Thus, we aim to clarify the relationship between MACC1 and EMT in NPC prognosis. Material and Methods: We performed immunohistochemical examination of tissue sections from 128 NPC patients that were divided into six groups corresponding to high and low protein expression of MACC1 and two EMT-related proteins, vimentin and E-cadherin, and Kaplan–Meier (KM) survival analyses were performed. Results: KM survival analysis showed that upregulation of MACC1 and vimentin and downregulation of E-cadherin were significantly associated with reduced survival in NPC. MACC1 overexpression was significantly correlated with poor 5-year overall survival, metastasis-free survival, and disease-free survival (P<0.05) but not with poor relapse-free survival (P>0.05). Univariate analyses revealed that MACC1, E-cadherin, and vimentin levels along with T and N tumor classifications and cancer staging are significant prognostic factors of NPC (P<0.05). Conclusion: Our findings showed the association between MACC1 and EMT in NPC malignancy and support the role of MACC1 as a prognostic biomarker and molecular target for NPC treatment.